Prostate cancer – Advantages and disadvantages of MR-guided RT. (September 2019) - Murray, Julia; Tree, Alison C.
Abstract: External beam radiotherapy for prostate cancer is an optimal treatment choice for men with localised prostate cancer and is associated with long term disease control in most patients. Image-guided prostate radiotherapy is standard of care, however, current techniques can include invasive procedures with imaging of poor soft tissue resolution, thus limiting accuracy. MRI is the imaging of choice for local prostate cancer staging and in radiotherapy planning has been shown to reduce target volume and reduce inter-observer prostate contouring variability. The ultimate aim would be to have a MR-only workflow for prostate radiotherapy. Within this article, we discuss these opportunities and challenges, relevant due to the increasing availability of MR-guided radiotherapy. Prospective multi-centre studies are underway to determine the feasibility of MR-guided prostate radiotherapy and daily adaptive replanning. In parallel, development and adaptation of the existing radiotherapy multidisciplinary workforce is essential to enable an efficient and effective MR-guided radiotherapy workflow. This technology potentially provides us with the anatomical and biological information to further improve outcomes for our patients.